Characterization of Fowlpox virus in chickens and bird-biting mosquitoes: a molecular approach to investigating Avipoxvirus transmission. (25th March 2019) - Yeo, Gladys; Wang, Yifan; Chong, Shin Min; Humaidi, Mahathir; Lim, Xiao Fang; Mailepessov, Diyar; Chan, Sharon; How, Choon Beng; Lin, Yueh Nuo; Huangfu, Taoqi; Fernandez, Charlene Judith; Hapuarachchi, Hapuarachchige Chanditha; et al.
Abstract : Avian pox is a highly contagious avian disease, yet relatively little is known about the epidemiology and transmission of Avipoxviruses. Using a molecular approach, we report evidence for a potential link between birds and field-caught mosquitoes in the transmission of Fowlpox virus (FWPV) in Singapore. Comparison of fpv167 ( P4b), fpv126 (VLTF-1), fpv175–176 (A11R-A12L) and fpv140 (H3L) gene sequences revealed close relatedness between FWPV strains obtained from cutaneous lesions of a chicken and four pools of Culex pseudovishnui, Culex spp. (vishnui group) and Coquellitidea crassipes caught in the vicinity of the study site. Chicken-derived viruses characterized during two separate infections two years later were also identical to those detected in the first event, suggesting repeated transmission of closely related FWPV strains in the locality. Since the study location is home to resident and migratory birds, we postulated that wild birds could be the source of FWPV and that bird-biting mosquitoes could act as bridging mechanical vectors. Therefore, we determined whether the FWPV-positive mosquito pools ( n =4) were positive for avian DNA using a polymerase chain reaction-sequencing assay. Our findings confirmed the presence of avian host DNA in all mosquito pools, suggesting a role for Cx. pseudovishnui, Culex spp. (vishnui group) and Cq. crassipes mosquitoes in FWPV transmission. Our study exemplifies the utilization of molecular tools to understand transmission networks of pathogens affecting avian populations, which has important implications for the design of effective control measures to minimize disease burden and economic loss.